A Lanthanide MOF Thin‐Film Fixed with Co3O4 Nano‐Anchors as a Highly Efficient Luminescent Sensor for Nitrofuran Antibiotics. Issue 43 (30th May 2017) - Zhang, Feng; Yao, Hua; Chu, Tianshu; Zhang, Gaowei; Wang, Yi; Yang, Yangyi
Abstract: Nitrofurans are a group of widely used veterinary antibiotics, which have been banned due to antibiotics pollution. Development of a rapid and effective method for the detection of nitrofuran antibiotics (NFAs) is an important challenge. Herein, we designed a chemical sensor based on a thin‐film composed of the lanthanide metal‐organic framework (Ln‐MOF) {[Eu2 (BCA)3 (H2 O)(DMF)3 ]⋅ 0.5DMF⋅ H2 O}n (Eu‐BCA, in which BCA is 2, 2′‐biquinoline‐4, 4′‐dicarboxylate) coated on a cost‐effective stainless steel wire mesh (SSWM) by Co3 O4 nano‐anchor fixation method. The MOF coatings were well adhered to the SSWM, resulting in a three‐dimensional porous, flexible, and processable sensor. The structure of the as‐prepared MOF thin‐film was confirmed by powder X‐ray diffraction (PXRD), and the surface morphology was examined by scanning electron microscopy (SEM). Significantly, the Eu‐BCA thin‐film was highly selective and sensitive to NFAs, and yet remained unaffected by other common antibiotics that may be present. The limits of detection for nitrofurantoin (NFT) and nitrofurazone (NFZ) are 0.21 and 0.16 μm, respectively. NFAs were also successfully detected in water from the Pearl River in Guangzhou, and from bovine serum samples. Hence, the reported Ln‐MOF thin‐film is a promising sensor for the detection of NFAs, thereby helping to protect human beings from all manner of hazards that arise from the abuse of antibiotics in livestock breeding. Abstract : A new detective : A Ln MOF thin‐film was fabricated using a nano‐anchor fixation method, in which cobalt oxide species serve as the anchor. This material was utilized as a highly selective sensor for the detection of common nitrofuran‐based antibiotics.